B-H curve tracer - Capuyan, Dennis Teodorico C. (2004)
Various information like permeability, coercivity, saturation flux and many others of transformer cores are observed from their BH curves. This project is capable of plotting the BH curve of various transformer cores as X-Y plots of an oscilloscope. Four transformer cores such as CS330075, FEE285, PQ3535 and EER-35A are analyzed using this setup. Calibration was done on each core tested to make use of the BH curve display. The computed permeabilities of the linear region of the cores were compared with that indicated in their corresponding datasheets to verify the accuracy of the display and are found to be accurate within 2 percent.